The effect of competitive strategies, organizational learning and business on the development of new services in chain stores - Reza Moradi Latrei; Naser Yazdani (مطالعات مدیریت راهبردی, 2023)
Introduction:Increasing competition in the current era and facing diverse and changing needs and demands of customers and the possibility of change and innovation in the products offered by companies in the service sector, which is due to the flexible nature of these products, make innovation and providing new services very important. It has made it important and necessary. New services can be considered as the core of competitive advantages of companies. Adapting to a turbulent environment requires a constant stream of new product development and delivery. Services are an indispensable part of every economy, and all successful economies, including industrial and commercial economies, owe a high share of their national gross product to the service sector. The increasing growth of this field and the consequent development of competition between companies are among the factors that highlight the importance of developing new services. The truth is that without paying attention to improving services and providing new services, organizations can never experience a sustainable and favorable growth for a long time. Due to many changes (such as the development of markets, globalization, changes in the rules of competition in industries and technological advances) that have affected the service industry, companies have both the opportunity and the need to use their skills and resources in a creative way to use there are potential and unprecedented advantages of this field. The development of new services is a set of activities that lead to partial or total changes and modifications in providing services to different parts of the market. Due to rapid changes in the state of technology and customer preferences, organizations cannot always rely on their existing services. Based on this, in the current research, the impact of competitive strategies, organizational learning and business on the development of new services has been investigated.Methodology:The research is an applied one in terms of its purpose, and a descriptive (non-experimental) one in terms of the nature or method of data collection, from the branch of field studies. The data collection tool is a researcher-made questionnaire using the indicators obtained from the research background. The content validity of the questionnaire was confirmed by the opinion of experts and professors, and the reliability of the questionnaire was confirmed through Cronbach's alpha coefficient, which was more than 0/899. The statistical population of this research is the managers of chain stores in Tehran province, including 699 stores from the chain stores of Ofogh Koresh, Shahrvand, Refah, Etka, Fruit and Vegetable Squares, Hyper Star, Najm Middle East, Hypersun, Hyperme, Iran Mall., Shahr Farash, and the number of samples was selected using the available cluster random sampling method and using Cochran's formula, 248 chain stores. Data analysis was done using the structural equation modeling approach.Results and Discussion:According to the purpose of this research to investigate the impact of competitive strategies, organizational learning and business on the development of new services in chain stores of Tehran province, the findings of this research show that competitive strategies, organizational learning and business have an effect on the development of new services in chain stores in Tehran province.ConclusionTherefore, these are suggested: 1. Senior managers who have the competence to build culture, be the pioneers of an internal revolution and a new dynamic, the alignment of individual goals and strategic goals will facilitate the strategy implementation process, and the adoption of a suitable strategy requires change whether we like it or not that directing and managing this change requires an adequate understanding of human resources.2. People who have capabilities in their field of work be given the necessary space to grow in the stores because it causes the growth of the store. 3. In the store, employees should be given the necessary training to learn and apply business strategy so that they can improve in their field of work. 4. By improving the quality and suitable human resources, high learning can be achieved, which will lead to the achievement of the focus strategy and can cause the retention and attraction of customers. 5. Personnel should provide services in new ways and benefit from new and updated technology compared to other competitors, and also remove existing old methods and procedures in order to achieve differentiation. 6. Managers should focus their activities in line with the chosen strategy and organize the necessary management decisions and actions. 7. Managers should prepare a comprehensive and coordinated action plan according to the organizational goals in the next 5 years that they are involved in drafting. It is better for these programs to be evaluated and operationally controlled in the expected time according to the allocated budget and the progress of the program.8. The personnel should have a proper way of dealing with the requests of the customers and have a customer-oriented culture and proper attention to the demands of the customers so that the customers buy the things they need. 9. The implementation of appropriate management methods using business strategy leads to the increase of service development, and finally, reducing the price of services increases the competitiveness of stores. 10. Redesigning jobs prevents employees from wasting their time, and also selecting and hiring the most qualified people provides profitable areas and reducing store costs. 11. Increasing the quality of providing technical guidance and how to inform about the store's product and service capabilities. 12. The necessary guidance should be provided transparently to perform requested services through the training of store personnel to increase customer satisfaction and ultimately sales. 13. Increasing the quality of providing services and solving product problems, as well as timely delivery and determining the duration of solving problems and how to inform in the store. 14. Regular handling of customer complaints and differentiation in the warranty period of their products compared to similar products in the store.